The IUGA/ICS classification of synthetic mesh complications in female pelvic floor reconstructive surgery: a multicenter study - John R. Miklos (2018)
© 2015, The International Urogynecological Association. Introduction and hypothesis: The objective was to report patterns of sling and transvaginal mesh-related complications using the IUGA/ICS classification of prosthesis-related complications. Methods: This was a retrospective chart review of all patients who underwent surgical removal of sling, transvaginal mesh, and sacrocolpopexy for mesh-related complications from 2011 to 2013 at three tertiary referral centers. The International Urogynecological Association (IUGA)/International Continence Society (ICS) classification system was utilized. Results: We identified 445 patients with mesh complications, 506 pieces of synthetic mesh were removed, and 587 prostheses-related complications were classified. 3.7 % of patients had viscus organ penetration or vaginal exposure as their presenting chief complaint and 59.7 % were classified as not having any vaginal epithelial separation or category 1. The most common category was spontaneous pain (1Be: 32.5 %) followed by dyspareunia (1Bc: 14.7 %). The sling group was 20 % more likely to have pain compared with the pelvic organ prolapse (POP) mesh group (OR 1.2, 95 % CI 0.8–1.6). The most commonly affected site (S2) was away from the suture line (49 %). Compared with the sling group, the POP group had a higher rate of mesh exposure, which mostly occurred at the suture line area. The majority of patients presented with mesh-related complications more than 1 year post-insertion (T4; average 3.68 ± 2.47 years). Conclusion: Surgeons should be aware that patients with vaginal mesh complications routinely exhibit complications more than 1 year after the implantation with pain as the most common presenting symptom.